VIBRATION ANALYSIS OF A TURBOCHARGER WITH AN ADDITIVELY MANUFACTURED COMPRESSOR WHEEL - Artur ANDREARCZYK; Paweł BAGIŃSKI (Scientific Journal of Silesian University of Technology. Series Transport)
This article presents the vibration analysis of a turbocharger, whose compression wheel was manufactured using a high-precision additive manufacturing technology. Currently, there are advance studies around the world for the development of parts of innovative fluid-flow machines using additive manufacturing techniques. The experimental research was carried out under conditions of reduced flow temperatures. The tests and the analysis were performed on a wheel manufactured using a 3D printing technology and on a conventionally used aluminium wheel. Apart from an FFT analysis of the vibration signal during machine operation, a machine run-up test was conducted (up to a speed of 105,000 rpm). The results showed the positive impact of the use of a plastic wheel on the dynamics of the system at a certain speed range, which might contribute to the development of a new method to optimise the geometry of flow systems in small high-speed turbomachines. A modified automotive turbocharger was subjected to experiments on a test stand.